Effects of Interleukin-1β Inhibition on Blood Pressure, Incident Hypertension, and Residual Inflammatory Risk: A Secondary Analysis of CANTOS. Issue 2 (February 2020) - Rothman, Alexander MK; MacFadyen, Jean; Thuren, Tom; Webb, Alastair; Harrison, David G; Guzik, Tomasz J.; Libby, Peter; Glynn, Robert J.; Ridker, Paul M.
Abstract : While hypertension and inflammation are physiologically inter-related, the effect of therapies that specifically target inflammation on blood pressure is uncertain. The recent CANTOS (Canakinumab Anti-inflammatory Thrombosis Outcomes Study) afforded the opportunity to test whether IL (interleukin)-1β inhibition would reduce blood pressure, prevent incident hypertension, and modify relationships between hypertension and cardiovascular events. CANTOS randomized 10 061 patients with prior myocardial infarction and hsCRP (high sensitivity C-reactive protein) ≥2 mg/L to canakinumab 50 mg, 150 mg, 300 mg, or placebo. A total of 9549 trial participants had blood pressure recordings during follow-up; of these, 80% had a preexisting diagnosis of hypertension. In patients without baseline hypertension, rates of incident hypertension were 23.4, 26.6, and 28.1 per 100-person years for the lowest to highest baseline tertiles of hsCRP ( P >0.2). In all participants random allocation to canakinumab did not reduce blood pressure ( P >0.2) or incident hypertension during the follow-up period (hazard ratio, 0.96 [0.85–1.08], P >0.2). IL-1β inhibition with canakinumab reduces major adverse cardiovascular event rates. These analyses suggest that the mechanisms underlying this benefit are not related to changes in blood pressure or incident hypertension. Clinical Trial Registration—: URL: https://clinicaltrials.gov . Unique identifier: NCT01327846. Abstract : Supplemental Digital Content is available in the text.